KARAKTERISTIK POMPA SENTRIFUGAL ALIRAN CAMPUR DENGAN VARIABLE FREQUENCY DRIVE - Handayani, Sri Utami (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2013)
In an industry that uses large centrifugal pumps continuously, pump speed setting can reduce energy consumption significantly. By changing the speed of a centrifugal pump,Â capacity, head, and pump power required will change according to pump affinity laws. Speed of a centrifugal pump can be changedÂ by variable frequency drive . This study aimed to investigate the characteristics of mixed flow centrifugal pumps with variable frequency drive. The results showed that 10% of maximum speed reduction can decrease power consumtion until 50%, while the increase in the efficiency is maximum 7.2%. The power reduction is different for different speed reduction. In a dynamic head dominated system the efficiency will remain constant during speed reduction while in static head dominated system will change.